Efecto del estado de excepción en tiempo de pandemia (covid-19) en la condición física de los habitantes de la Parroquia Camilo Ponce, cantón Babahoyo, de la Provincia de los Ríos año 2021 - Poveda Gomez, Erick Orlando (2021)
The purpose of this research work is to present a Didactic Guide of essential exercises for the health of the inhabitants of the Camilo Ponce Parish of the City of Babahoyo, with the improvement of physical condition due to the COVID-19 pandemic, and that due to this situation, people were kept in a state of exception and could not leave their homes due to being infected with this virus and endangering their loved ones or those around them. For this research project we will provide significant knowledge by executing a descriptive investigation, observing the reality of the problems or situation in which we find ourselves at the time of obtaining different aspects of the opinions of the surveyed inhabitants, they allowed us to conclude that for reasons of the COVID - 19, they cannot exercise any physical activity or in the spaces where they reside. This guide is designed to facilitate the development of various exercises that everyone can do without any inconvenience.